Impact of Environmental Responsibility and Environmental Knowledge on Green Consumption Intention: A Mediated-Moderation Analysis - Muhammad Wasim (JCMS, 2024)
This study was aimed at examining the impact of environmental responsibility and environmental knowledge on green consumption intention with the mediating role of environmental concern and the moderating role of green product availability in the relationship between environmental concern and green consumption intention. The current studies on the factors influencing green consumption have greatly advanced in the past few years. However, limited efforts have been undertaken to examine the influence of consumer’s environmental responsibility and environmental knowledge on green consumption intention and the manner in which this relationship is explained through the lens of environmental concern and green product availability especially when the consumers are becoming more environmentally aware and are depicting an increased willingness to buy green products. For this purpose, a questionnaire method was used to obtain data from 328 Pakistani consumers of green cosmetic and personal care products. A PLS-SEM technique was applied to assess the validity of the research hypotheses. The results indicate that environmental responsibility has a positive effect on environmental concern and green consumption intention. Environmental knowledge does not have any significant impact on green consumption intention. However, environmental knowledge has a positive effect on environmental concern and environmental concerns mediates the relationship between environmental responsibility, environmental knowledge and green consumption intention. Moreover, it was observed that green product availability does not moderate the relationship between environmental concern and green consumption intention. The theoretical and managerial implications along with limitations and future research directions have also been discussed.